The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13293-016-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender in medical education: a national student survey

Abstract: BackgroundGender- and sex-specific medicine is defined as the practice of medicine based on the understanding that biology (dictated by sex chromosomes) and social roles (gender) are important in and have implications for prevention, screening, diagnosis, and treatment in men and women. In light of the many ways that sex and gender influence disease presentation and patient management, there have been various initiatives to improve the integration of these topics into medical education curriculum. Although cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 14 publications
2
38
0
6
Order By: Relevance
“…In this study, there were minor gender differences in assessment results and their self‐report of content training in medical school and residency. Jenkins et al . published the results of a national student survey on sex and gender in medical education, which found that male medical students reported a higher exposure rate to SGBM content during their training than female medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there were minor gender differences in assessment results and their self‐report of content training in medical school and residency. Jenkins et al . published the results of a national student survey on sex and gender in medical education, which found that male medical students reported a higher exposure rate to SGBM content during their training than female medical students.…”
Section: Discussionmentioning
confidence: 99%
“…A Web‐based survey of residency graduates and program directors in EM residency programs found that more than half of the participants reported that their SGBM instruction was inadequate and that gender differences in conditions seen in the emergency department were relevant to their clinical practice . In contrast, the survey also found that only 16.3% of program directors felt that SGBM content was a priority within the curriculum, and 76.6% felt that other curricular demands were an obstacle to integration of SGBM content into the curriculum . The SAEM SGEM toolkit has been designed to address these gaps in EM residency education and to provide solutions to facilitate integration of SGBM into residency curricula.…”
Section: Discussionmentioning
confidence: 99%
“…The multi‐station approach provided students with opportunities to affirm their learning with experts in a safe learning environment, reflected by the students' openness in sharing personal stories. Students clarified their own and popular perceptions of gender and sexuality, thereby demystifying gender and sexuality in medical school . Such safe environments would be particularly beneficial for students who may have unresolved feelings about their own gender or sexual identities …”
Section: Discussionmentioning
confidence: 99%
“…Gender and sexuality warrant substantial discussion in medical education, as they play significant roles in patient management . Gender and sexuality awareness is important for good clinical practice, and for the quality of care provided, particularly for people of gender and sexual minorities (non‐binary and/or non‐heterosexual), whose sexual and social stigma cause distinct health care disparities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation